2013
DOI: 10.1111/jocn.12101
|View full text |Cite
|
Sign up to set email alerts
|

Condom‐use intentions and the influence of partner‐related barriers among women at risk for HIV

Abstract: These findings have important implications for nurses as they are uniquely positioned to facilitate HIV risk reduction among their patients through the discussion of sexual health issues and barriers to negotiating condom use that women may confront.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Sexual relationship power in these studies as outlined by Bonacquisti, et al[30] “is a construct that characterizes power differentials between intimate partners, encompassing relationship dynamics such as trust, commitment, infidelity, decision-making and condom use negotiation”. We found 7 studies that pertained to this theme (refer to Table 2), four of which were quantitative, and three qualitative in design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual relationship power in these studies as outlined by Bonacquisti, et al[30] “is a construct that characterizes power differentials between intimate partners, encompassing relationship dynamics such as trust, commitment, infidelity, decision-making and condom use negotiation”. We found 7 studies that pertained to this theme (refer to Table 2), four of which were quantitative, and three qualitative in design.…”
Section: Resultsmentioning
confidence: 99%
“…[3033] Violence in intimate relationships was measured differently for each study (refer to Table 2). Condom use practices and/or confidence in condom use negotiation were assessed in all 4 of the studies, again through study specific questions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that condom use is a multifaceted issue, particularly in sexual relationships involving power differentials and perceived monogamy. For example a study conducted by Bonacquisti & Geller [24] showed that when women's preference to use condoms was compared to their report of actual condom-use behavior, significant discrepancies emerged, indicating that women often are not in control of this aspect of their sexual behavior [24]. Moreover, another study showed that among 1,252 women enrolled, 78.4% were married (of whom 15.1% were in polygamous unions), 1.4% had a known HIV-infected partner, and 33.6% partner of unknown HIV status.…”
Section: Recommendations For Hiv Prevention and Treatmentmentioning
confidence: 99%
“…The SRPS has primarily been applied to nonsubstance using heterosexual partnerships in the field of HIV prevention research (Campbell et al, 2009; Conroy et al, 2016; Muldoon, Deering, Feng, Shoveller, & Shannon, 2015), in which lower SRPS scores have been associated with higher risk and inconsistent condom use and for HIV infection (Bonacquisti & Geller, 2013; Dunkle et al, 2004; Jewkes, Dunkle, Nduna, & Shai, 2010). However, we are unaware of any investigation of relationship dynamics in the intersecting injecting and sexual relationships of young WWID, or one that quantifies the impact of sexual relationship power on injecting or sexual risk behaviors in the context of WWID’s sexual relationships.…”
Section: Introductionmentioning
confidence: 99%